Small-Bowel Lesions in Patients Taking Direct Oral Anticoagulants Detected Using Capsule Endoscopy - Minoru Yamaoka; Hiroyuki Imaeda; Naoki Hosoe; Kazuaki Yoneno; Ryu Kanno; Takashi Mitsufuji; Takahiro Sasaki; Yuji Akiyama; Hideki Ohgo; Yuichi Morohoshi; Takanori Kanai; Toshimasa Yamamoto; et al. (Gastroenterology Research and Practice)
Background and Aim. Direct oral anticoagulant- (DOAC-) induced small-bowel lesions have not been described. We evaluated small-bowel lesions related to DOAC using video capsule endoscopy (VCE). Methods. This study was a prospective, open-label, nonblinded, multicenter, and observational study. From September 2013 to March 2017, patients taking DOACs were enrolled. Patients underwent VCE. The type and location of small-bowel lesions were registered. Also, (1) the proportion of lesions detected between types of DOAC was evaluated and (2) the hemoglobin (Hb) and serum ferritin levels were compared between patients with and without small-bowel lesions. Results. 33 patients were enrolled, but 4 patients withdrew their consent, and VCE was performed on 29 patients. Eight, 13, and 8 patients received dabigatran, rivaroxaban, and apixaban, respectively. Small-bowel transit was complete in 27 of 29 patients (93.1%). Small-bowel lesions were detected in 23 (79.3%), redness in 12 (41.4%), erosions in 14 (48.3%), and angioectasia in 3 (10.3%) patients, and 6 patients (20.7%) had no abnormalities. Redness and erosions were detected in the upper, middle, or lower portions, but erosions tended to be less frequent in the middle portion (p=0.25, 0.06). Angioectasia was not detected in the lower portion. No patients had active bleeding. The findings did not differ according to the drug. The relationships between the endoscopic findings and the Hb and serum ferritin levels were not significant. Conclusion. Many patients taking DOACs had small-bowel lesions; however, most lesions were relatively mild. Observing small-bowel lesions over longer periods may be necessary in patients taking DOACs. This trial is registered with UMIN000011527.